Efficacy and safety of first- versus second-generation Bruton tyrosine kinase inhibitors in chronic lymphocytic leukemia: a systematic review and meta-analysis - Ke, Liyuan; Li, Su; Huang, Danxue; Wang, Yan (Frontiers in Pharmacology, 2024)
We conducted this first systematic review and meta-analysis aimed to assess the competitive advantage of second-generation Bruton tyrosine kinase inhibitor (BTKi) compared to first-generation BTKi in chronic lymphocytic leukemia (CLL). Literature search was conducted from PubMed, Web of Science, Embase databases and hematology annual conferences. Data of over response rate (ORR), progression-free survival (PFS) and overall survival (OS) were extracted to pool meta-analysis of efficacy, meanwhile adverse events (AEs) were extracted to pool meta-analysis of safety. Bias risk assessment and meta-analysis were performed by Review Manager 5.3 and STATA 14 software. A total of 3649 patients from twenty-nine cohorts were included. The results showed benefits of ORR and 24-month PFS in 2nd-generation BTKi compared to 1st-generation BTKi were not significant in the whole population, only significant in the relapsed or refractory (R/R) CLL patients subgroup (ORR: 86.4% vs. 76.2%, p=0.013; p=0.004). Any-grade AEs were comparable between 1st-and 2nd-generation BTKi, but grade 3 or high AEs were significantly less frequent with 2nd-generation BTKi versus 1st-generation BTKi (grade 3 or high: 53.1% vs. 72.5%; p=0.002). Headache was more frequent with 2nd-generation BTKi, while diarrhoea and atrial fibrillation were more frequent with 1st-generation BTKi. Only for patients with relapsed or refractory CLL, 2nd-generation BTKi has a competitive advantage, while adverse effects still need to be considered.